A fifth-millennium BCE sanctuary at Tol-e Chega Sofla in the northern Persian Gulf. (September 2021) - Moghaddam, Abbas
Abstract: While the evidence from late prehistoric monumental contexts from southwestern Iran have been relatively indirect, recent excavation at Tol-e Chega Sofla in the northern Persian Gulf, sheds some light on this issue by providing a collection of symbolic features presumeably representing one of the earliest sanctuaries so far documented from a fifth millennium BCE context in southwestern Iran. Such complex ritual behavior is indicated by a number of backed brick structures, stone steles, animal scarification pits as well as distinctive pottery vessels unearthed in the northern mound of Tol-e Chega Sofla (Area C).